#TITLE_ALTERNATIVE# - WIJAYANTO (NIM 25004035); Pembimbing : I Wayan Sengara, Ir, MSE, Ph.D., NURRACHMAD
Abstract: In the geotechnical earthquake engineering, there were several methods have been developed to analyze seismic loading on the distribution of dynamic lateral earth pressure on rigid wall, whereas those methods were based either on experimental study or analytical formulation upon the behaviour of rigid retaining wall system. The assumption frequently taken on those studies was the wall base considered to be absolutely fixed, in which this is not the case on basement wall, considering the fact that the basement wall is not absolutely fixed. During the earthquake, there were relative motions occurred between wall and surrounding soil, which eventually results in the soil-structure interaction effect on the basement system. This study analyses the distribution of dynamic lateral earth pressure on basement wall and amplification of earthquake motion on the surface using finite element method. Dynamic soil-structure interaction analyses were done using PLAXIS Dynamics software. This research is focused on parametric study in order to analyze the sensitivity upon the variation of soil condition, peak base acceleration, frequency content of input motion, depth of basement, depth of baserock and the stiffness of basement structure. The variations in soil condition are homogenous clay deposit based on UBC 1997 site classification C, D and E for stiff soil, medium-stiff soil and soft soil, respectively. Result of the analyses indicated that the distribution of dynamic lateral earth pressure reach its maximum value on the basement wall with almost linear pressure increments on soft soil and non-linear pressure increments on medium-stiff and stiff soil. The highest pressure increase is occurred at four-fifth depth of wall basement measured from the top to the base of the wall. Another result from this study is the basement structure which was constructed on a soil deposit, would not influence the dynamic stiffness of the soil-basement structure system, otherwise it would influence the geometrical damping of the system. On this study, the recommendation of seismic lateral load distribution considering the soil condition variations and peak base acceleration are also provided.